Multifarious Uses of UV-VIS Spectroscopy for Green Synthesis of Silver Nanoparticles for Antibacterial Textiles - Toufique Ahmed; R. Tugrul Ogulata; Osman Gülnaz (Textile & Leather Review, 2024)
Green synthesis is an easy and economical method of synthesizing silver nanoparticles (AgNPs). However, many variables, including the ideal temperature, the volume and concentration of silver nitrate, the amount of plant extract, etc., affect the green synthesis. This article aims to determine the ideal temperature and plant extract amount using the UV-VIS spectrum. It was found above 40 °C was required for both Calendula arvensis (field marigold) leave extract and silver nitrate to synthesize AgNPs. The optimum temperatures were 55 °C and 60 °C for AgNO3 and plant extract, respectively and it was determined using Taguchi orthogonal array based on the UV-VIS spectrum. Silver nanoparticles (AgNPs) can be incorporated into textiles by padding and in-situ methods, but they need accurate plant extract amounts for good antibacterial efficiency. Two equations were proposed for determining the optimum plant extract amount for padding and in-situ methods. Several AgNPs loaded samples were prepared following the derived equations. For evaluating the efficiency of the equations C.reticulata (orange) peel extract was used besides C.arvensis plant extract. The samples were also characterized by antibacterial tests, Scanning Electron Microscope (SEM), Energy Dispersive Spectroscopy (EDS), and X-ray diffraction (XRD). It showed when plant extract was taken according to the equations, around 45 nm nanoparticle size and 100% antibacterial activity were obtained. However, taking 1 ml more plant extract than that of the calculated amount of plant extract increased nanoparticle size to 107 nm and reduced antibacterial activity to 90%.